Absent Aortic Valve Associated with Double Outlet Right Ventricle and Aortopulmonary Window: Physiologic Implications of a Rare Malformation in both the Fetus and Neonate. (22nd May 2013) - Sabati, Arash A.; Wong, Pierre C.; Randolph, Linda; Pruetz, Jay D.
Abstract Absence of the aortic valve is a rare congenital heart defect that is detectable in the prenatal period. In this condition, functional aortic valve leaflets are absent; in their place are rudimentary, immobile noncoapting plate‐like structures at the level of the annulus resulting in severe aortic regurgitation. We report the fetal diagnosis and subsequent postnatal course of an infant with the novel association of absent aortic valve, double outlet right ventricle, and aortopulmonary window. This unique combination of defects resulted in an unusual pattern of circular shunting that produced evidence of fetal heart failure. Shortly after birth, the abnormal physiology led to compromised systemic perfusion, intestinal perforation and subsequent rapid demise of the patient. Abrupt postnatal deterioration typifies the vast majority of the absent aortic valve cases found in the literature. Our patient is unique in that it is the first female reported with absent aortic valve and the first reported with an aortopulmonary window. This report demonstrates that absent aortic valve is a condition that can be diagnosed prenatally by fetal echocardiogram; the highly abnormal physiology places these patients at risk for fetal heart failure. Given the potential for clinical instability and rapid deterioration after birth, such patients should undergo rapid postnatal assessment and immediate surgical intervention when deemed appropriate.